Akuntabilitas Pemerintahan Desa Sekongkang Bawah Dalam Pengelolaan Anggaran Pendapatan Dan Belanja Desa (APBDes) Kecamatan Sekongkang Kabupaten Sumbawa Barat - Zitri, Ilham (JIAP (Jurnal Ilmu Administrasi Publik), 2022)
Accountability for the management of the Village Revenue and Expenditure Budget is an ongoing problem in the village which shows that the village government system that has been in effect until now has not proven to be a good system, this problem is proof that there are still many problems regarding the management of the village income and expenditure budget in many village governments. . The goal is how to account for the management of the income and expenditure budget of Sekongkang Bawah Village, Sekongkang District, West Sumbawa Regency, while the method used is a combination that combines two methods, the techniques used are interviews, questionnaires and documentation. The results of this study are that the village government is still unable to manage the Village Revenue and Expenditure Budget in Sekongkang Bawah Village. The first problem faced by Sekongkang Bawah Village is the limited or limited ability of village officials or human resources in managing the village income and expenditure budget or the absence of participation from the village community itself which makes the problems multiply. This condition is clearly seen from the recognition of the difficulties of the village government in managing the village income and expenditure budget due to the lack of experts in the planning, implementation or accountability process, this is also seen by the village community who argues that the management of the Village Revenue and Expenditure Budget is still not good, and there are many expectations of the village community so that the next planning or process can be carried out properly by the village government.